The Third Plan Mid-Term Appraisal Government of India Planning Commission November, 1963 - Planning Commission (Planning Commission, 1963)
The Third Five Year Plan was conceived as the first phase of a period of intensive development leading towards a self-reliant and self-generating economy. The Plan also sought to give a more precise content to the social objectives of the Constitution and to ensure a significant advance towards the achievement of socialism and of equal opportunity for every citizen. Planned development during the preceding decade had laid the foundation for rapid economic growth. Accordingly, the Third Plan postulated an increase in agricultural production of 30 per cent, in industry of 70 per cent and in national income of 30 percent. Over the past two years, the national effort has been larger and more broad-based than before. Though the advances made in several basic branches of industry, including steel.
Government of India Planning Commission